UNLOCKING POTENTIAL: A SECONDARY DATA PERSPECTIVE ON FDI IN INDIAN HIGHER EDUCATION – OPPORTUNITIES, CHALLENGES, AND FUTUREDIRECTIONS - 1. Mrs. Sonal Asher , 2. Prof. (Dr.) Yogesh Joshi, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
This study investigates Foreign Direct Investment (FDI) in Indian higher education using a secondary data analysis approach, focusing on opportunities, challenges, and future directions. By synthesizing insights from government reports, academic studies, industry whitepapers, and global organizations, the research highlights the transformative potential of FDI to enhance infrastructure, encourage innovation, and foster international collaborationsin higher education. It identifies significant challenges, such as regulatory hurdles, quality assurance issues, and socioeconomic disparities, that limit the effectiveness of FDI in this sector. The findings emphasize the need for streamlined regulatory frameworks, public-private partnerships, and investments in digital education to maximize the benefits of FDI. Furthermore, this research provides actionable recommendations for policymakers, educational institutions, and investors, aligning FDI strategies with the goals of India’s National Education Policy (NEP) 2020 to ensure equitable access and quality enhancement in higher education. By contributing to the growing discourse on globalization and education, this study underscores the importance of a strategic and inclusive approach to FDI, offering valuable insights for the sustainable development of Indian higher education.